An investigation of the risks of using new integrated accounting information system: a case study of Zimbabwe Statistical Agency - Gumbura, Farai (Midlands State University, 2015)
The accounting information system (AIS) is of utmost important in providing the financial information for decision making purposes within the organisation. The research explores on the risks of using new integrated (AIS) and the effect of operating non- integrated accounting information systems. For the past years the ZIMSTAT has been facing challenges due to the operation of non- integrated (AIS), various departments operated stand- alone systems divorced from each other. The organisation has been faced with risks such as data manipulation, errors, and perpetration of frauds by the system users taking advantage of the weak system and results in poor decision making. The research showed that the degree of non-integrated (AIS) is very high at the organisation though integrated systems Enterprise Resource Planning (ERP) were in place. To encourage users to adapt to change, management was encouraged to show high levels of commitment and there was need for the users to be trained regularly in and outside the working environment. There is also need to appoint a project team which will monitor the progress of the implementation project.